Supporting Student Wellness to Enable Resiliency During the COVID-19 Pandemic (Emerging Perspectives: Interdisciplinary Graduate Research in Education and Psychology, 2021)
The COVID-19 pandemic has created a unique time, requiring flexibility to adapt to evolving circumstances. The shift from being fully immersed as a doctoral student on campus, to being a full-time mother and online student at home and largely isolated, was a significant and challenging change. Paradoxically, I was filled with gratitude for additional immediate family time while I also felt incredible stress due to a lack of dedicated professional time. Determined to persevere, I embraced three strategies that fostered my resilience during the COVID-19 pandemic: (1) listening to course content; (2) dedicating time to daily physical activity; and (3) spending time outdoors. Moving forward, I will continue to prioritize my wellness by embracing the strategies identified here, and I encourage universities to explore how student wellness can be more comprehensively and proactively supported.